2008
DOI: 10.1002/msc.147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multidisciplinary outpatient pain management programme based at a community hospital

Abstract: The result of the evaluation indicated that this PMP, delivered in a community hospital setting, made some significant differences to patients with intractable chronic pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Community hospitals provide a wide range of services, covering the whole spectrum of care provision, from preventative [2021] and primary care [2223], through to outpatient services [242526], inpatient medical care [2728], surgery [2930], minor injury [31] and accident and emergency care [2232]. Within these broad areas, there was considerable diversity of the types of services provided, and a number of studies further reported on the implementation of new and innovative types and methods of service provision not previously available within the community hospital setting, such as point-of-care testing [23], fracture clinics [33] or chemotherapy [34].…”
Section: Resultsmentioning
confidence: 99%
“…Community hospitals provide a wide range of services, covering the whole spectrum of care provision, from preventative [2021] and primary care [2223], through to outpatient services [242526], inpatient medical care [2728], surgery [2930], minor injury [31] and accident and emergency care [2232]. Within these broad areas, there was considerable diversity of the types of services provided, and a number of studies further reported on the implementation of new and innovative types and methods of service provision not previously available within the community hospital setting, such as point-of-care testing [23], fracture clinics [33] or chemotherapy [34].…”
Section: Resultsmentioning
confidence: 99%
“…Community hospitals provide a wide range of services, across a broad spectrum of care provision, from preventative 38,39 and primary care 40,41 through to outpatient services, [42][43][44] inpatient medical care, 21,45 surgery, 46,47 minor injury care 48 and accident and emergency (A&E) care. 40,49 Within these broad areas, there was considerable diversity of the types of services provided, and a number of studies further reported on the implementation of new types and methods of service provision not previously available within the community hospital setting, such as point-of-care testing, 41 fracture clinics 50 or chemotherapy.…”
Section: Range Of Services Provided By Community Hospitalsmentioning
confidence: 99%
“…d = 1 13 compare favourably with these values. With regard to healthcare utilisation, Wong et al 66 found a significant reduction in pain-related GP visits following a multidisciplinary CBT PMP ( . , . )…”
Section: Comparison With Other Studiesmentioning
confidence: 99%